Reappropriating the Trincheira-Bacaja Indigenous Land - Xikrin, Bepkyi; Bollettin, Paride [UNESP] (Univ Basilicata, 2022)
This photo essay aims to describe the process of reappropriation of a part of the Trincheira-Bacaja Indigenous Land by the Mebengokre in September 2021, after almost three years of its invasion by not-indigenous people. The images were taken by Bepkyi Xikrin when the Mebengokre have been able to return to the area after the partial removal of the invaders. The perceptions and sensations of the invasion's impacts on the environment, as well as the participation of the people in this collective recuperation highlight the social dimension of the environment as well as the resistance of the Mebengokre resistance and their struggle for their lives, lands and rights.
Keywords: Mebengokre; Amerindians; land occupation; land recuperation; Amazon; deforestation